Selective adsorption of L1210 leukemia cells/human leukocytes on micropatterned surfaces prepared from polystyrene/polypropylene-polyethylene blends - Gengec, Nevin Atalay; Gulsuner, Hilal Unal; Erbil, H. Yildirim; Tekinay, Ayse Begum (Elsevier Science Bv, 2014)
The objective of this study is to prepare polymeric surfaces which will adsorb L1210 leukemia cells selectively more than that of healthy human leukocytes in order to develop new treatment options for people with leukemia. Chemically heterogeneous and micropatterned surfaces were formed on round glass slides by dip coating with accompanying phase-separation process where only commercial polymers were used. Surface properties were determined by using optical microscopy, 3D profilometry, SEM and measuring contact angles. Polymer, solvent/nonsolvent types, blend composition and temperature were found to be effective in controlling the dimensions of surface microislands. MIT tests were applied for cell viability performance of these surfaces. Polystyrene/polyethylene-polypropylene blend surfaces were found to show considerable positive selectivity to L1210 leukemia cells where L1210/healthy leukocytes adsorption ratio approached to 9-fold in vitro. Effects of wettability, surface free energy, microisland size geometry on the adsorption performances of L1210/leukocytes pairs are discussed. (C) 2013 Elsevier B.V. All rights reserved.
Keywords: Micropatterning; L1210 leukemia cells; Leukocytes; Selective cell adhesion; Contact angle